2020
DOI: 10.1080/07421222.2020.1759974
|View full text |Cite
|
Sign up to set email alerts
|

Decision Problems in Blockchain Governance: Old Wine in New Bottles or Walking in Someone Else’s Shoes?

Abstract: Blockchain technology comes with the promise of being a disruptive technology with the potential for novel ways of interaction in a wide range of applications. Following broader application, scholarly interest in the technology is growing, though an extensive analysis of blockchain applications from a governance perspective is lacking to date. This research pays special attention to the governance of blockchain systems and illustrates decision problems in 14 blockchain systems from four application domains. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 86 publications
0
57
0
Order By: Relevance
“…The establishment of blockchain consortia was a reaction to the strong urgency of cooperation between involved stakeholders . How exactly organizations work together and find solutions within these new form of collaboration are not yet fully understood (Ziolkowski et al, 2020). However, empirical results indicate that preexisting collaboration among stakeholders positively affects the adoption of blockchain (Queiroz and Fosso Wamba, 2019).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The establishment of blockchain consortia was a reaction to the strong urgency of cooperation between involved stakeholders . How exactly organizations work together and find solutions within these new form of collaboration are not yet fully understood (Ziolkowski et al, 2020). However, empirical results indicate that preexisting collaboration among stakeholders positively affects the adoption of blockchain (Queiroz and Fosso Wamba, 2019).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Similar to how Nakamoto envisioned blockchain would transform money and payments, Santiso [77] articulated his hope that blockchain would be the silver bullet in fighting global corruption. In reviewing the emerging literature on the topic, we found either technically oriented abstract work, for example, about a consensus algorithm [50] and cryptocurrencies [37,67,86], or domain-specific work covering the Internet of Things [23], e-identification [85], shipping [41], maritime sector [72], health care [2], the food supply chain [4647], governance issues [97], and the choice of blockchain technology [121314]. However, this existing research deals with limited aspects of blockchain, featuring few applications that demonstrate the fact that the real transformative power of blockchain lies in "its openness and technologically driven capability to pervade multiple vertical layers of [the] digital ecosystem infrastructure" [33].…”
Section: Blockchain In Global Supply Chainmentioning
confidence: 99%
“…Interestingly, multiple studies reviewed have suggested mixed or contradictory effects of IT on corrupt and fraudulent activities [see, for instance , 84]. Recently, blockchain has been promoted as a revolutionary technology with the capacity to lower uncertainty, insecurity, and ambiguity in business transactions by providing single truth for all network participants [13,16,48,66,97]. This has led thought leaders such as Santiso [77] to wonder "Can it [blockchain] be a game changer in the global fight against corruption?"…”
Section: Introductionmentioning
confidence: 99%
“…Blockchains can differ in the ways in which the consensus in the network is achieved, what kind of currency is used, and how security and privacy are achieved [30]. Two criteria that are also often used to classify blockchains are access to transactions and access to the validation of transactions [31,32]. In public permissionless blockchains, all participants can read, submit, and validate transactions.…”
Section: Blockchainmentioning
confidence: 99%